2017
DOI: 10.1016/j.flatc.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Perylene-based non-covalent functionalization of 2D materials

Abstract: The surfactant assisted exfoliation and non-covalent functionalization of twodimensional layered materials, like graphene, transition metal dichalcogenides, etc., has extraordinarily been propelled forward within the last 5 years. Numerous molecules have been designed and attached to the exfoliated layers, and based on their outstanding properties, perylene based dyes have become one of the most frequently used π-detergents. Therefore, the prospect of this micro review is to summarize the most prominent achiev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 138 publications
(134 reference statements)
3
41
0
Order By: Relevance
“…[25,26] Despite synthetic efforts,t he chemistry and therefore the molecular doping of antimonene remains completely unexplored. In relation to that, we have recently reported on the noncovalent functionalization of BP with electron-poor and polarizable polycyclic aromatic molecules, thus observing ar emarkable charge-transfer behavior, and improving the resistance of the flakes against oxygen degradation.[ 27,28] In this context, the present work nicely illustrates,for the first time,the noncovalent functionalization of antimonene with ap erylene bisimide (PDI;F igure 1a), thereby showing amore pronounced charge-transfer behavior …”
supporting
confidence: 57%
See 2 more Smart Citations
“…[25,26] Despite synthetic efforts,t he chemistry and therefore the molecular doping of antimonene remains completely unexplored. In relation to that, we have recently reported on the noncovalent functionalization of BP with electron-poor and polarizable polycyclic aromatic molecules, thus observing ar emarkable charge-transfer behavior, and improving the resistance of the flakes against oxygen degradation.[ 27,28] In this context, the present work nicely illustrates,for the first time,the noncovalent functionalization of antimonene with ap erylene bisimide (PDI;F igure 1a), thereby showing amore pronounced charge-transfer behavior …”
supporting
confidence: 57%
“…[ 27,28] In this context, the present work nicely illustrates,for the first time,the noncovalent functionalization of antimonene with ap erylene bisimide (PDI;F igure 1a), thereby showing amore pronounced charge-transfer behavior …”
supporting
confidence: 52%
See 1 more Smart Citation
“…These observations can significantly improve the scope and possible application of black phosphorus as well as other pnictogens since its stability towards oxidation exhibit one of the most important issue. The non‐covalent functionalization of various 2D materials by large aromatic molecules based on perylene was recently summarized; however, the field of pnictogens remains almost completely unexplored with the exception of BP . An interesting donor–acceptor pair was created by Chen et al.…”
Section: Modificationsmentioning
confidence: 99%
“…For example, pyrene derivative was promising in improving the dispersion of graphene. This stabilizer provided strong π‐π overlap with the graphene surface and can achieve good compatibility between GO and the polymer matrix . Some studies were also revealed that carbon nanotubes were successfully exfoliated in ionic liquids, especially, imidazolium‐based ionic liquids were used as alternative polar solvents for carbon materials exfoliation .…”
Section: Introductionmentioning
confidence: 99%